-6(-5p-1)=12p+6(-5p+1)

Simple and best practice solution for -6(-5p-1)=12p+6(-5p+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(-5p-1)=12p+6(-5p+1) equation:



-6(-5p-1)=12p+6(-5p+1)
We move all terms to the left:
-6(-5p-1)-(12p+6(-5p+1))=0
We multiply parentheses
30p-(12p+6(-5p+1))+6=0
We calculate terms in parentheses: -(12p+6(-5p+1)), so:
12p+6(-5p+1)
We multiply parentheses
12p-30p+6
We add all the numbers together, and all the variables
-18p+6
Back to the equation:
-(-18p+6)
We get rid of parentheses
30p+18p-6+6=0
We add all the numbers together, and all the variables
48p=0
p=0/48
p=0

See similar equations:

| −8d+2=−40d+2 | | 25=8+b | | 3u+16=-6 | | 25=8=b | | -10(5a-1)-2(12a+5)=-2a+6a | | 2x=-8.6 | | -y-3=32-6y | | 14x+1=2x+7 | | 10r=-110 | | 4(2k+6)=-7k+39 | | 17=6x–1 | | -4+2r-5r=17 | | y=39-3(y/3-3) | | -2d-20=-10 | | -4+3=x-7 | | 2r+5r=21 | | 15x-17=21 | | -2v+4(3v-6)=-40-6v | | 7x=2x+300 | | 23.96x+6.99=76.51x+1.99 | | 4*x+12=9 | | 23.96+6.99x=76.51+1.99x | | -221+9x=115-3x | | 4(1+3a)-4=27+3a | | (x^2-5)(4-x)=0 | | 1299.99+89.99x=699.99+49.99x | | 25–3(4–2d)=0 | | 1299.99+89.99=699.99+49.99x | | 45+135x=180 | | 2x^2+20+44=0 | | 3g+8=47 | | 6(2y–3)+4=10 |

Equations solver categories